تحليل نموذج العمل الرقمي للمساعدات الرقمية الصوتية في الخدمات المصرفية - لزغد، صلاح الدين; بوالقدرة ،نزيهة (جامعة الوادي University of Eloued, 2025)
Voice digital assistant services have become a pivotal part of digital transformation in the banking sector. However, research on innovative digital business models for these services remains limited. This study aims to bridge this gap by analysing, tracking, and evaluating the digital business model of the voice digital assistant services of the Turkish bank Garanti BBVA, known as MIA. The findings indicate that this technology has significantly improved operational efficiency, enhanced customer satisfaction, and expanded the scope of digital services. The experience of Garanti BBVA has confirmed the strength and validity of the applied digital business model for voice digital assistants in banking services.
Analysis of the Digital Business Model for Voice Digital Assistants in Banking Services: A Case Study of Garanti BBVA
مقال
Keywords: المساعدات الرقمية الصوتية; التحول الرقمي; نموذج العمل الرقمي; Digital Voiceassistants; Voice Bankingservices; digital transformation